Efficiency and Equity: A General Equilibrium Analysis of Rent-Seeking - Ben J. Heijdra; Pim Heijnen (Center for Economic Studies and ifo Institute (CESifo), 2021)
We study the rent-seeking phenomenon using a simple, static general equilibrium model. The economy consists of two sectors, both employing a constant returns-to-scale technology with labor as its sole input. One of the sectors is a monopoly, where a continuum of agents compete for a share of monopoly profits (i.e. rent). Agents are heterogeneous in labor productivity and rent-seeking ability: they face a choice between engaging in (productive) work or vying for a share of the rent (i.e. a contest against other rent-seekers). At the aggregate level, rent-seeking reduces the available amount of labor in the economy and thereby lowers output and welfare (rent-seeking is inefficient). At the individual level, rent-seeking shifts income towards rent-seekers. Consequently, an economy with few rent-seekers tends to have high income inequality: an effect that is exacerbated by the fact that rent is decreasing in the number of rent-seekers (low levels of rent-seeking increase inequity). This tradeoff between efficiency and equity is the primary focus of this paper. We investigate how the distribution of rent-seeking ability and the correlation between labor productivity and rent-seeking ability shape this tradeoff.
Keywords: D62; D63; D72; E13; 330; rent-seeking; economic waste; inequality; monopolization; contest